BUDAYA SPIRITUAL ALIRAN KEJAWEN â€œPRASETYO MANUNGGAL KARSOâ€ SEBAGAI WUJUD PLURALISME KEPERCAYAAN MASYARAKAT DI BOYOLALI - Alan Sigit Fibrianto (Penamas, 2019)
Prasetyo Manunggal Karso is one of the many beliefs of kejawen in Java. Prasetyo Manunggal Karso is a community that teaches kejawen flow and is located in Sub-District Banyudono, Boyolali Regency. Like Kejawen faith trust in general, Prasetyo Manunggal Karso has some grip itself in his teachings as a means to get closer to the God is the creator of the entire universe. In this paper, seeks to explain the intricacies of the teachings of the beliefs of Kejawen Prasetyo Manunggal Karso, some of them concerning, their background and history, the scriptures used, the principal teachings, the way of worship, the instruments used in rituals, and ways of spreading the teachings. In addition, the researchers also tried to analyze the findings with the perspective of the theory of habitus and cultural reproduction of the sociologist, Pierre Bourdieu. This paper aims to examine the cultural practices of the genus of Kejawen Prasetyo Manunggal Karso, using qualitative descriptive method, with key informant Mr. Toto Soeharto as the founder of the kejawen community of Prasetyo Manunggal Karso in Boyolali. The result show that the presence of Kejawenâ€“Prasetyo Manunggal Karso is a form of wealth of Indonesian characteristic, a portrait of religious diversity, as well as a distinctive style of Javanese spiritual culture as part of the Indonesian national identity.